Optimization of the multidisciplinary care flow for children with learning difficulties - Nessy, Vanessa Maciel; Simões, Wagner Lourenzi (Brazilian Journal of Production Engineering, 2024)
This case study analyzes the multidisciplinary care process for children with learning difficulties in the urban school network, highlighting the importance of special and inclusive education. The simulation was conducted using data from 2023 and identified neurology as the primary bottleneck. The new simulation doubled neurology’s capacity, increased the number of children examined, and reduced the waiting time. Investing in continuous training, incorporating new technologies, and optimizing processes is essential not only to ensure inclusion but also to address the educational challenges affecting our children. Through simulations, it was found that by increasing the capacity in one department with the addition of one professional, 332 more students could be served per year, eliminating the current deficit of 327 students per year. We obtained a significant reduction on the total time to complete the entire process, it makes the flow more efficient and decreased the time between the student’s entry into the process and notification from 68.47 days to 42.28 days.